2023
DOI: 10.1021/acs.biomac.2c01469
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Theranostic Nanomedicine for In Situ Self-Boosting Cancer Photochemotherapy

Abstract: Although traditional nanomedicines have enhanced the therapeutic efficacy and improved the survival quality of cancer patients, random drug release and drug resistance are deep-rooted problems hindering their clinical application. A precise nanoplatform combing chemotherapy and photodynamic therapy (PDT) is developing as a new therapeutic strategy to overcome the above challenges. Herein, a novel supramolecular nanomedicine is ingeniously constructed for in situ selfboosting cancer photochemotherapy. Hydrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 37 publications
(42 reference statements)
0
5
0
1
Order By: Relevance
“…The combination of aromatic macrocyclic compounds and CLRP has led to innovative developments in the design of biomacromolecules for disease treatment. , Aromatic macrocyclic compounds are well-known for their multifaceted biocompatibility and remarkable biological activities, making them suitable for use in polymeric drug systems and synergistic treatment. ,, Studies have shown promising results regarding the efficacy of these biomacromolecules in treating various diseases such as cancer, , cardiovascular disorders, and wound healing . The PET-RAFT process, which utilizes catalysts derived from aromatic macrocyclic compounds, has significantly advanced the field, enabling the development of novel designs and applications.…”
Section: Bioapplicationsmentioning
confidence: 99%
“…The combination of aromatic macrocyclic compounds and CLRP has led to innovative developments in the design of biomacromolecules for disease treatment. , Aromatic macrocyclic compounds are well-known for their multifaceted biocompatibility and remarkable biological activities, making them suitable for use in polymeric drug systems and synergistic treatment. ,, Studies have shown promising results regarding the efficacy of these biomacromolecules in treating various diseases such as cancer, , cardiovascular disorders, and wound healing . The PET-RAFT process, which utilizes catalysts derived from aromatic macrocyclic compounds, has significantly advanced the field, enabling the development of novel designs and applications.…”
Section: Bioapplicationsmentioning
confidence: 99%
“…[64][65][66] In addition to targeted delivery, these supramolecular vesicles can also effectively boost and manipulate the generation of singlet oxygen species (ROS) for antibacterial applications when photosensitizers, such as porphyrins and particular types of AIEgens, are incorporated into the vesicular structures. [67][68][69] Therefore, the modification of photosensitizers onto macrocycles or the encapsulation of guest molecules with ROS productivity by macrocycles is broadly performed to afford supramolecular nanocarriers with controllable photosensitizing ability, 70 whereby the loading and controlled release of antibiotics are also accessible in the meantime. 71…”
Section: Supramolecular Nanocarriers Based On Macrocyclesmentioning
confidence: 99%
“…Similarly, it has significant implications for the regulation of drug resistance ( Vincent et al, 2022 ). Based on the anatomical and pathophysiological differences between normal and tumor cells, the NPs have strong enhanced permeability and retention (EPR) effect, as shown in Figure 2 ( Ikeda-Imafuku et al, 2022 ; Wu et al, 2023 ). Nanocarriers can be divided into natural polymer and synthetic polymer materials, most of which have excellent biocompatibility, stability, safety, non-toxicity and modifiability, mainly including virus-like particles, poly lactic glycolic acid (PLGA), liposomes, dendrimers, metal organic framework compounds, as shown in Figure 3 ( Guo and Jiang, 2020 ; Ji et al, 2023 ).…”
Section: Strengths Of Nanodrug In Nsclc Treatmentmentioning
confidence: 99%